Global gene regulation during activation of immunoglobulin class switching in human B cells - Zhang, Youming (Sci Rep, 2016)
Immunoglobulin class switch recombination (CSR) to IgE is a tightly regulated process central to atopic disease. To profile the B-cell transcriptional responses underlying the activation of the germinal centre activities leading to the generation of IgE, naïve human B-cells were stimulated with IL-4 and anti-CD40. Gene expression and alternative splicing were profiled over 12 days using the Affymetrix Human Exon 1.0 ST Array. A total of 1,399 genes, forming 13 temporal profiles were differentially expressed. CCL22 and CCL17 were dramatically induced but followed a temporal trajectory distinct from classical mediators of isotype switching. AICDA, NFIL3, IRF4, XBP1 and BATF3 shared a profile with several genes involved in innate immunity, but with no recognised role in CSR. A transcription factor BHLHE40 was identified at the core of this profile. B-cell activation was also accompanied by variation in exon retention affecting >200 genes including CCL17. The data indicate a circadian component and central roles for the Th2 chemokines CCL22 and CCL17 in the activation of CSR.